PENGARUH PENGGUNAAN MODEL EXAMPLES NON EXAMPLES TERHADAP KETERAMPILAN MENULIS DESKRIPSI SEKOLAH DASAR - Putri Saraswati; Siti Halidjah; Sugiyono Sugiyono (Universitas Tanjungpura, 2019)
AbstractThe problem in this study was how does the use of non examples of model use for writing description skills of fourth grade students of West Pontianak 55 State Elementary School ?. This study aims to analyze the magnitude of the effect of using the examples of non-examples models on description writing skills of fourth grade students of West Pontianak 55 State Elementary School. The method used in this study was the experimental method. The form of research used was quasi experimental design with a non equivalent control group design pattern. From data and data analysis, the type of research used was quantitative research. This study used a sampling technique that was by sampling technique. The data collection tool used was a test. The population is all students from two classes totaling 60 students, while the sample was class IVA and class IVB which amounts to 60 students. Based on the data analysis, the results of the experimental class post-test average = 70.68 and the results of the post-test control class average = 61.79. This shows the influence of students in learning to write descriptions using the examples non examples model. After t-test was obtained tcount 4.83 for dk 58 and α = 5% obtained t table was 1.68, which means Ttest and ttable, then Ha was accepted, which means there was a significant effect on the use of examples non examples models. From the calculation of the effect size (ES), obtained (ES) of 0.8 with medium criteria, this means that the use of examples of non-examples models has a moderate influence on students' description writing skills.Keywords: Influence, Examples Non Examples, Writing Description skills.